Configuraciones de poder en la novela “Las tres ratas” de Alfredo Pareja Diezcanseco - Hernández Alvarado, Esther Jocelyn (2024)
The present research entitled Configurations of Power in the novel "Las Tres Ratas" had the primary objective of analyzing the figure of power in this novel by the Ecuadorian writer Alfredo Pareja Diezcanseco from this literary reference. The whole research is supported, and it was found that there are power configurations within the work. Following the theme of the present study, we proceeded to analyze similar investigations that serve as a reference to support the work to develop the research. As a next step, we moved to investigate historical, scientific information to determine consubstantial elements as referents of the theoretical framework and, from this perspective, strengthen the scientific support of the research work. As for the approach of the methodology, it was qualitative since a subjective point of view was used in the analysis of characters; it was of non-experimental design, so there was no type of manipulation within the research; it was descriptive since it was analyzing an event, it was also documentary since the information from other authors was collected to strengthen the research, it was also transversal since the data was collected in a specific time, Finally, in the methodology, hermeneutics was used to interpret the characters and to analyze each one of them in terms of the figures of power, which is the theme of the research. To conclude the research, a discussion was carried out concerning the configuration of power in the work "Las tres ratas" by Pareja Diezcanseco, with which it was possible to confirm that there is power among the characters at certain moments of the work. Still, it was concluded that there are types of power, which were analyzed in detail in the discussion and analysis.